Liquefaction characteristics of offshore wind turbine with hybrid monopile foundation via centrifuge modelling. (January 2020) - Wang, Xuefei; Zeng, Xiangwu; Li, Xinyao; Li, Jiale
Abstract: Some offshore wind farms are built in seismically active areas. The offshore wind turbine (OWTs) are high-rise structures and sensitive to lateral failures during the earthquake. In this study, an innovative hybrid monopile foundation is proposed for OWTs. A series of centrifuge shake table tests is conducted to investigate the seismic response and liquefaction characteristics of the hybrid monopile foundation. Mechanisms of the seismic behavior of soil, lateral displacements of the wind turbine, and structural settlements are evaluated. Centrifuge test results indicate that the liquefaction around the hybrid monopile foundation is weakened compared to the traditional single pile. The soil partially keeps its strength and stiffness during the shaking due to the higher confining stress. The lateral stability of the system is enhanced. OWTs with the hybrid monopile foundation tends to settle more during the earthquake due to the soil-structure interaction and the static bearing induced soil shearing. Two types of hybrid monopile foundations are constructed with different weights and materials, which are predominant influence factors for their seismic response. This study aims to investigate the seismic behavior of the hybrid monopile foundation for OWTs during earthquake events and provide references for practical designs. Highlights: An innovative hybrid monopile foundation for offshore wind turbine is proposed. Liquefaction characteristics of the foundation are investigated by a series of centrifuge tests. Mechanisms of lateral stability and settlement for the wind turbine are demonstrated. Interactions between soil and wind turbine under the earthquake are illustrated.